Significance of nodal metastatic tumor characteristics in nodal metastasis and prognosis of patients with invasive ductal carcinoma of the breast - Hasebe, Takahiro; Sasaki, Satoshi; Imoto, Shigeru; Ochiai, Atsushi (Cancer science, 2003)
There is no study evaluating the significance of nodal metastatic tumor characteristics in tumor progression of invasive ductal carcinomas (IDCs) of the breast. The purpose of this study was to investigate whether nodal metastatic tumor characteristics play an important role in the tumor progression of IDCs. The subjects of this study were 205 IDC patients with nodal metastases. Significant associations with increased numbers of nodal metastases, and patient outcomes were evaluated by multivariate analyses, in comparison with well‐known histological parameters. The numbers of lymph nodes with extra‐nodal invasion and with extra‐nodal blood vessel tumor emboli, the distance of extra‐nodal blood vessel tumor emboli from the nodes, and the nodal tumor dimensions significantly increased the number of nodal metastases in the multivariate analysis (P<0.001). Cox multivariate analyses showed that the parameters which significantly increased hazard rates (HRs) of disease‐free survival (DFS), distant organ metastasis (DOM) and overall survival were 6 or more mi‐totic figures of nodal metastatic tumors (P<0.05). Six or more lymph nodes with extra‐nodal invasion, and an extra‐nodal blood vessel tumor emboli dimension of >0.6 mm significantly increased the HRs of DFS and DOM in multivariate analyses (P<0.05). The present study demonstrated the important roles of nodal metastatic tumors in the tumor progression of IDCs. (Cancer Sci 2003; 94: 181–187)